Gridded fossil CO2 emissions and related O2 combustion consistent with national inventories 1959–2018 - Jones, Matthew W.; Andrew, Robbie M.; Peters, Glen P.; Janssens-Maenhout, Greet; De-Gol, Anthony J.; Ciais, Philippe; Patra, Prabir K.; Chevallier, Frederic; Le Quéré, Corinne (Scientific data, 2021)
Quantification of CO 2 fluxes at the Earth’s surface is required to evaluate the causes and drivers of observed increases in atmospheric CO 2 concentrations. Atmospheric inversion models disaggregate observed variations in atmospheric CO 2 concentration to variability in CO 2 emissions and sinks. They require prior constraints fossil CO 2 emissions. Here we describe GCP-GridFED (version 2019.1), a gridded fossil emissions dataset that is consistent with the national CO 2 emissions reported by the Global Carbon Project (GCP). GCP-GridFEDv2019.1 provides monthly fossil CO 2 emissions estimates for the period 1959–2018 at a spatial resolution of 0.1°. Estimates are provided separately for oil, coal and natural gas, for mixed international bunker fuels, and for the calcination of limestone during cement production. GCP-GridFED also includes gridded estimates of O 2 uptake based on oxidative ratios for oil, coal and natural gas. It will be updated annually and made available for atmospheric inversions contributing to GCP global carbon budget assessments, thus aligning the prior constraints on top-down fossil CO 2 emissions with the bottom-up estimates compiled by the GCP. Measurement(s) carbon dioxide emission • oxygen combustion Technology Type(s) digital curation • computational modeling technique Factor Type(s) annual and monthly fossil carbon dioxide emissions estimates • annual and monthly oxygen combustion estimates Sample Characteristic - Environment climate system Sample Characteristic - Location global Machine-accessible metadata file describing the reported data: https://doi.org/10.6084/m9.figshare.13333643